Characteristic of Tobacco mosaic virus isolated from cucumber and tobacco collected from East Java, Indonesia - LISTIHANI; SRI HENDRASTUTI HIDAYAT; SURYO WIYONO; Tri Asmira Damayanti (Society for Indonesian Biodiversity, 2019)
Abstract. Listihani, Hidayat SH, Wiyono S, Damayanti TA. 2019. Characteristic of Tobacco mosaic virus isolated from cucumber and tobacco collected from East Java, Indonesia. Biodiversitas 20: 2937-2942. Tobacco mosaic virus (TMV) is a newly emerging virus infecting cucumbers in Java, Indonesia. The basic characters of the TMV isolated from cucumber need further study to investigate its differences with that from tobacco. Thus, the research aimed to study the character of both isolates based on their biological, symptomatology and nucleic acid of coat protein (CP) gene properties. The TMV isolates from both cucumber and tobacco were able to infect similar indicator plants with differing symptom expressions, especially on eggplant. Homology of nucleotide and amino acid of coat protein gene among isolates were about 90.3% and 91.0%, and homology to other isolates was about 87.6 to 93.8% and 89.3 to 96.8%, respectively. There were 17 amino acid differences in the CP gene which is presumed to differentiate those two isolates. Phylogenetic analysis CP gene sequences compared with corresponding isolates in GenBank showed the two isolates separated in different clades. The cucumber isolate from Kediri is closely related to tomato isolate from China in clade I, while tobacco isolate from Jember closely related to tobacco isolate from China in clade IIindicating the existence of two differ TMV variants. It will increase the difficulty to manage TMV in the fields.